The joint AU-EU Innovation Agenda: when Science, Technology and Innovation (STI) stand for Sustainable Tangible Impact - Lorusso, Vincenzo; Venturi, Piero; Seke, Lukovi; Teshome, Mahlet; Idinoba, Monica, Ebele; Masheleni, Hambani; Buisman, Nienke; Hoegel, Jens (My University, 2022)
Outcome of the African Union (AU) – European Union (EU) Research & Innovation (R&I) Ministerial Meeting of July 2020, the “AU-EU Innovation Agenda” aims to turn R&I investments into tangible businesses, services and jobs. This Agenda proposes specific objectives with short-, medium- and long-term actions for all four priority areas of the AU-EU cooperation in Science, Technology and Innovation (STI), namely (i) Public Health, (ii) Green Transition, (iii) Innovation and Technology and (iv) Capacities for Science. This paper aims to raise awareness on the AU-EU Innovation Agenda and the ongoing public consultation on its working document (open until 30 June 2022). This consultation will gather feedback and input from citizens, stakeholders and their respective organisations, through an online survey (https://ec.europa.eu/eusurvey/runner/IAPublicConsultation). This is done to ensure that the Agenda will address actual unmet needs on the ground, to ultimately maximise chances to provide for sustainable and inclusive growth in Africa and Europe.
Keywords: Africa; Agriculture; AU; Capacity Building; Climate Change; Development; Education; EU; Europe; Global Health; Global Health Diplomacy; Green Transition; Innovation; International cooperation; International Development; Public Health; R&D; Science; Science Diplomacy; Sustainable Energy; Technology